The Importance of Examining the Impact of Health Sector Expenditure Growth on Total Factor Productivity (Case Study: Iranian Provinces) - Salehzadeh, Tooran; Akbari Moghadam, Beitollah; Mousavi, Mirhossein; Mirzapour, Akbar; Hadizadeh, Arash (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to investigate the impact of healthcare expenditure growth on total factor productivity (TFP) across Iranian provinces.Methodology: The study employs a panel data approach using provincial-level data from 2000 to 2017. The dataset includes variables such as healthcare expenditure, GDP per capita, urbanization rates, and demographic indicators. Econometric models are applied to examine the relationship between healthcare expenditures and TFP growth in Iran’s provinces. Additionally, the study controls for other factors that could influence TFP, such as educational attainment and industrialization levels.Findings: The results indicate that healthcare expenditure growth has a significant positive effect on TFP in most provinces, with a stronger impact observed in more urbanized and economically developed regions. The study also finds that healthcare spending contributes to productivity improvements primarily through enhanced human capital and better workforce health, with varying effects across different regions of the country.Conclusion: The findings suggest that healthcare expenditures play a crucial role in enhancing productivity at the provincial level, especially in areas with higher urbanization and better access to healthcare services. Policymakers should consider targeted investments in healthcare infrastructure and human capital development to maximize the economic benefits of healthcare spending. The study highlights the need for regional strategies to address healthcare disparities and promote sustainable economic growth through improved public health.